Exploring the Dynamics of Islamic Thoughts at MHM Lirboyo Kediri on Inter-Religious Relations through Bahsul Masail Analysis - M. Ikhsanudin (LP2M IAI Miftahul Ulum Pamekasan, 2024)
This article examines the views and dynamics of the students’ thoughts at the Lirboyo Islamic Boarding School in Kediri regarding inter-religious relations. The study was conducted only at the Madrasah Hidayatul Mubtadi’in (MHM) Pondok Pesantren Lirboyo Kediri because this boarding school is highly productive in publishing its legal opinions and serves as a barometer for the East Java and Central Java. The study aims to understand the students’ views at MHM the Lirboyo on these issues through an analysis of the legal opinions produced by the boarding school. The qualitative study primarily focuses on a literature review of published legal opinions supported by semi-structured interviews. In the issue of inter-religious relations, several issues have been comprehensively discussed, such as the issue of peace and religious pluralism, inter-religious marriage, the appointment of non-Muslim leaders, and the destruction of non-Muslim places of worship. From the discussion above, it appears that the MHM Lirboyo is still in the replacement model (exclusive) but is moving towards an inclusive attitude, allowing for tolerance in mu’amalah issues. Regarding non-Muslim leaders and marrying people of the book, the MHM Lirboyo prohibits it and categorizes it as forbidden and invalid. Meanwhile, in destroying non-Muslim places of worship, the Madrasah Hidayatul Mubtadi’in Lirboyo prohibits it regardless of the excuse, and the perpetrator can be given legal sanctions, either in the form of had (criminal law) or kafaroh. The method of legal discovery used by the MHM Pondok Pesantren Lirboyo emphasizes the istimbath bayani model with a diversification of texts model of Fiqh.